2009
DOI: 10.1016/j.ajog.2009.06.063
|View full text |Cite
|
Sign up to set email alerts
|

The maternal cortisol awakening response in human pregnancy is associated with the length of gestation

Abstract: The findings are the first to suggest that the hormonal (cortisol) response to a naturally occurring challenge (awakening) and the degree of attenuation of this response over the course of gestation may represent a novel biomarker of increased vulnerability for earlier birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 33 publications
8
78
2
Order By: Relevance
“…In this study, we showed in patients who ultimately delivered before term after being admitted for possible PL an inversion of the salivary cortisol diurnal biorhythm documented both on day 4 and 6, indicating a profound dysregulation of the HPA axis; this result extends earlier findings that cortisol awakening response is associated with shorter gestational length [10]. Conversely, women who delivered at term presented a physiological fluctuation of diurnal salivary cortisol with higher concentrations in the morning.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, we showed in patients who ultimately delivered before term after being admitted for possible PL an inversion of the salivary cortisol diurnal biorhythm documented both on day 4 and 6, indicating a profound dysregulation of the HPA axis; this result extends earlier findings that cortisol awakening response is associated with shorter gestational length [10]. Conversely, women who delivered at term presented a physiological fluctuation of diurnal salivary cortisol with higher concentrations in the morning.…”
Section: Discussionsupporting
confidence: 82%
“…Cortisol, a major product of hypothalamus-pituitary-adrenal (HPA) axis activity, is believed to be physiopathologically involved in the regulation of human pregnancy and parturition [4,5], fetal growth and maturation [4,6,7] and timing of delivery [8,9]. The degree of the attenuation of the physiological cortisol awakening response over the course of gestation has been proposed as a chronobiological marker of PL [10,11]. Although the diurnal regulation of HPA axis activity (with the level of cortisol in the morning being higher than in the evening) has been associated with maternal psychological well-being and normal fetal growth [12], no study to date has investigated the predictive role of a dysregulation in diurnal salivary cortisol pattern secretion in women with an assigned diagnosis of possible PL.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated risk for preterm delivery associated with an increase in stress or anxiety persisted when adjusting for obstetric risk, pregnancy related anxiety, ethnicity, parity, and prenatal life events. These findings suggest that women who do not show the expected or normative decline in stress responding are at increased risk for early delivery, an assumption that was confirmed by the findings from the study examining changes in the CAR across gestation described above (Buss et al, 2009c).…”
Section: Birth Outcomessupporting
confidence: 59%
“…For instance, stress experienced early in gestation, but not later, is associated with preterm birth Lederman et al, 2004). Moreover, women who fail to show the expected decrease in generalized stress and anxiety or dampening in the cortisol awakening response during pregnancy are at increased risk for preterm delivery (Buss et al, 2009b;Glynn et al, 2008).…”
Section: Alterations In Stress Responding During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation